The up-regulation of elongation factors in the barley leaf and the down-regulation of nucleosome assembly genes in the crown are both associated with the expression of frost tolerance - Janská, Anna; Aprile, Alessio; Cattivelli, Luigi; Zámečník, Jiří; de Bellis, Luigi; Ovesná, Jaroslava (Functional & integrative genomics, 2014)
We report a series of microarray-based leaf and crown transcriptome comparisons involving three barley cultivars (cvs. Luxor, Igri and Atlas 68) which express differing degrees of frost tolerance. The transcripts were obtained following the exposure of seedlings to low (above and below zero) temperatures, aiming to identify those genes and signalling/metabolic pathways which are associated with frost tolerance. Both the leaves and the crowns responded to low temperature by the up-regulation of a suite of abscisic acid (ABA)-responsive genes, most of which have already been recognized as components of the plant low temperature response. The inter-cultivar comparison indicated that genes involved in maintaining the leaf's capacity to synthesize protein and to retain chloroplast activity were important for the expression of frost tolerance. In the crown, the repression of genes associated with nucleosome assembly and transposon regulation were the most relevant transcriptional changes associated with frost tolerance, highlighting the role of gene repression in the cold acclimation response.
Keywords: nukleozomy; regulace genové exprese u rostlin; reakce na chladový šok; Hordeum; transkriptom; Transcriptional Elongation Factors; mapování chromozomů; Transcriptome; Freezing; rostlinné proteiny; Plant Leaves; Gene Expression Regulation, Plant; down regulace; Up-Regulation; upregulace; listy rostlin; Chromosome Mapping; zmrazování; transkripční elongační faktory; Down-Regulation; Genes, Plant; Plant Proteins; Nucleosomes; rostlinné geny; Cold-Shock Response; ječmen (rod)